Advanced thermoforming - Engelmann, Sven (John Wiley & Sons, 2012)
This guide gives an overview and insight into the advanced technology of thermoforming, discussing different processes and applications. It reveals the possibilities of thermoforming from forming, filling, and sealing processes, to using thermoforming technology for cost saving purposes and maximum efficiency. Its coverage addresses the simulation of formed parts as well as applications of technical parts and packaging. The reader is guided through the path of development, design, machine and mold technology and production, as well as the latest innovations, from thermoformed bottles to fully automated assembly lines